CD8 Binding of MHC-Peptide Complexes in cis or trans Regulates CD8+ T-cell Responses - Liu, Yang; Cuendet, Michel A; Goffin, Laurence; Šachl, Radek; Cebecauer, Marek; Cariolato, Luca; Guillaume, Philippe; Reichenbach, Patrick; Irving, Melita; Coukos, George; Luescher, Immanuel F (Journal of molecular biology, 2019)
The coreceptor CD8αβ can greatly promote activation of T cells by strengthening T-cell receptor (TCR) binding to cognate peptide-MHC complexes (pMHC) on antigen presenting cells and by bringing p56Lck to TCR/CD3. Here, we demonstrate that CD8 can also bind to pMHC on the T cell (in cis) and that this inhibits their activation. Using molecular modeling, fluorescence resonance energy transfer experiments on living cells, biochemical and mutational analysis, we show that CD8 binding to pMHC in cis involves a different docking mode and is regulated by posttranslational modifications including a membrane-distal interchain disulfide bond and negatively charged O-linked glycans near positively charged sequences on the CD8β stalk. These modifications distort the stalk, thus favoring CD8 binding to pMHC in cis. Differential binding of CD8 to pMHC in cis or trans is a means to regulate CD8+ T-cell responses and provides new translational opportunities.
Keywords: sekvence aminokyselin; Models, Molecular; antigeny CD8; Protein Binding; CD8 Antigens; MHC; mutace; Mice; histokompatibilní antigeny; T cell; Structure; CD8; myši knockoutované; Models, Biological; Peptides; CD8-pozitivní T-lymfocyty; aktivace lymfocytů; Protein Conformation; molekulární modely; Mutation; zvířata; vztahy mezi strukturou a aktivitou; Lymphocyte Activation; Protein Interaction Domains and Motifs; T-cell receptor; Amino Acid Sequence; vazba proteinů; interakční proteinové domény a motivy; Mice, Knockout; biologické modely; multiproteinové komplexy; myši; peptidy; Multiprotein Complexes; CD8-Positive T-Lymphocytes; Histocompatibility Antigens; Structure-Activity Relationship; konformace proteinů; Animals